Cultivating Honest Character in Social Context: The Basis for Realizing Academic Integrity - Wulandari, I Gusti Agung Ayu; Tristiantari, Ni Ketut Desia; Agetania, Ni Luh Putu (Indonesian Values and Character Education Journal, 2024)
Technological advances have a big impact on every line of life, including education. Everyone in the world of education can easily access information from various sources on the internet, this causes a lot of academic fraud to occur, including acts of plagiarism. GONE Theory, discovered by Jack Bologne in 1993, explains a theory about the factors that underlie someone's fraudulent or deceptive behavior. GONE is an abbreviation of Greed (greed), Opportunity (opportunity), Need (need and Exposure). The aim of this research is to determine the dominant influence between the 4 cheating factors. This type of research uses ex post facto with the population being active students in the Province Bali in 2023 who are studying under the auspices of the Ministry of Education, Research and Technology, namely from Ganesha Education University, Udayana University, Bali State Polytechnic, and the Indonesian Institute of Arts, based on data obtained from the Central Statistics Agency, there are 58,588 students (BPS, 2023). table from Krejcie and Morgan, the number of samples for a population of 50,000-75,000 is 382 (taken from N = 50,000-75,000 in Morgan's table) with an accuracy level (d2) of 95% and a significance level (z2) of 5 %. The research results show that the disclosure variable has the greatest influence on academic cheating, namely 39%. Based on these results, honest character is the best solution to create academic integrity among students.